1995
DOI: 10.3354/meps129151
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal studies of seston lipids in relation to microplankton species composition and scallop growth in South Broad Cove, Newfoundland

Abstract: ABSTRACT. The concentration and nutritional awlity of suspended particulate matter at an experimental scallop aquaculture site on the east -1 of Newfoundland, Canada, was determined at 3 depths over an 8 mo sampling period. Lip~d r-lassaand fatty acids were measured chromatographically and the seston components were identified and quantified by microscopy. These measurements were correlated and then related to the growth of j u l -d e scallops Placopecten magellanicus introduced to the site. The low seston con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 20 publications
0
38
1
Order By: Relevance
“…Laws 1991, Parrish et al 1995. Actively growing phytoplankton with an abundant supply of inorganic nutrients generally synthesize mainly protein and lesser amounts of storage compounds such as neutral lipids, carbohydrates and low molecular weight metabolites (Morris 1981, Laws 1991.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laws 1991, Parrish et al 1995. Actively growing phytoplankton with an abundant supply of inorganic nutrients generally synthesize mainly protein and lesser amounts of storage compounds such as neutral lipids, carbohydrates and low molecular weight metabolites (Morris 1981, Laws 1991.…”
Section: Introductionmentioning
confidence: 99%
“…Of the various macromolecular classes, lipids are of special interest for their nutritional importance to consumers and potential for contaminant transfer (Kattner et al 1989, Wainmann & Lean 1992, Parrish et al 1995. Nutrients and taxonomic affiliation both influence the proportion of fixed carbon that phytoplankton direct to lipids (Shifrin & Chisholm 1981, Madariaga 1992, Fernandez et al 1994a) and there has been some success in predicting lipid biosynthesis from environmental factors in freshwater phytoplankton communltles (Wainmann & Lean 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, net tow data presented here, from late summer and fall, are probably not representative of plankton at other times of the year. The typical seasonal pattern of phytoplankton abundance in cold North Atlantic nearshore waters shows diatom lipid markers dominating in spring, followed by terrestrial plant material, small flagellates, zooplankton, and bacterial sources becoming more important in late summer and fall (Mayzaud et al 1989, Parrish et al 1995. Seasonal changes in lipid composition of particulate matter can be caused by changes in taxonomic source or physiological changes within a taxonomic group (Mayzaud et al 1989).…”
Section: Net Towsmentioning
confidence: 99%
“…Rather, smaller flagellates, bacteria, and terrestrial material likely accounted for most of the seston. Parrish et al (1995) looked at seasonal seston microplankton species composition in South Broad Cove, Newman Sound. They also noted high levels of microzooplankton in the water column during summer, particularly after a storm mixing event.…”
Section: Net Towsmentioning
confidence: 99%
“…Since lipid classes are useful markers to determine sources and fate of organic matter in marine systems (Parrish, 1988) they have widely been used as biological tracers (Parrish et al, 1995;Derieux et al, 1998;Goutx et al, 2000), but only once in conjunction with bacterial community structure changes (Ghiglione et al, 2007). In the present study CCA analysis showed that dissolved lipids from chloroplast origin (LC), which indicate phytoplankton source of DOM (Goutx et al, 1990), were the main biotracer associated with bacterial community structure, due surely to their high concentration at particular samples of 5-20 m depths (Fig.…”
Section: Cca With Lipid Class Biotracersmentioning
confidence: 99%